To solve the system of equations using elimination with multiplication, you want to eliminate one variable by multiplying one or both equations by a constant so that when you add or subtract the equations, one of the variables cancels out.
Let's start by multiplying the second equation by 2:
-2x + 4y = 30
(2)(-2x + 4y) = (2)(30)
-4x + 8y = 60
Now, you can add the two equations together:
(4x - 6y) + (-4x + 8y) = -48 + 60
-6y + 8y = 12
2y = 12
y = 6
Substitute this value of y back into one of the original equations, let's use the first equation:
4x - 6(6) = -48
4x - 36 = -48
4x = -12
x = -3
Therefore, the solution to the system of equations is (x, y) = (-3, 6). So the correct answer is (−3, 6).
Solve the system of two equations using elimination with multiplication. 4x−6y=−48 −2x+4y=30 (1 point) Responses (3, 9) left parenthesis 3 comma 9 right parenthesis (−21,−6) left parenthesis negative 21 comma negative 6 right parenthesis (−3, 6) left parenthesis negative 3 comma 6 right parenthesis (−33,−9) left parenthesis negative 33 comma negative 9 right parenthesis
1 answer